Regioselective Transition‐Metal‐Free C(sp2)−H Borylation: A Subject of Practical and Ongoing Interest in Synthetic Organic Chemistry - Rej, Supriya; Chatani, Naoto (Angewandte Chemie International Edition, 2022)
Considerable advances have been made in the area of C−H functionalization in the last few decades. A number of approaches including both directed and nondirected strategies have been developed thus far. Among the various C−H functionalizations, C−H borylation is of special interest due to the wide applications of organoboron compounds. In this regard, various transition‐metal‐catalyzed regioselective strategies have been developed. However, the major concern regarding metal‐catalyzed C−H borylation procedures is the requirement of a precious metal as well as the contamination by metal precursors in the desired products, which limit the application of this process in large‐scale synthesis. Therefore, recent trends have involved the use of transition‐metal‐free systems. We summarize recent developments in transition‐metal‐free regioselective C−H borylation. We believe that this Review will help to increase interest in this field and stimulate further progress. Recent developments in strategies for transition‐metal‐free regioselective C−H borylation are summarized in this Review. Strategies developed to control the regioselectivity of the electrophilic borylation, such as approaches controlled by electronic effects, auxiliaries, and steric factors, are also discussed. EDG=electron donating group, DG=directing group, TM=transition metal.